Intelectual capital voluntary evidence: a study with novo mercado companies (Revista Brasileira de Contabilidade e Gestão, 2020)
The study aims to investigate the elements of voluntary disclosure of Intellectual Capital (CI) extracted from Management Reports (RAs) and to identify the frequency of such disclosure. The sample includes 05 companies listed on B3 (Brazil, Bolsa, Balcão) by the Novo Mercado segment. The research is characterized by its descriptive nature, the technical procedure adopted was the documentary research and the interpretation of the ARs had a quantitative and qualitative approach. The following results were observed: 100% of the sample companies showed CI elements; elements such as Education (40%) and Distribution Channel (21.62%) were highlighted in the frequency of disclosure. The most representative category was External Capital (36%). The company JBS S.A. was the company with the highest number of IC elements disclosed (31). In the comparison made with previous researches, there was an increase in disclosure, a greater concern was identified by companies in relation to the disclosure of IC. The study reinforces the idea about the difficulty of quantifying and measuring intellectual capital and also contributed to companies taking a new stance in relation to the treatment of intellectual capital.
Keywords: Intellectual Capital; Voluntary Disclosure; New Market